Hybrid Contract pada Syariah Card dalam Perspektif Ekonomi Islam - Khusnia, Chinta; Hisnidah, Mukaromatul; Khasanah, Umrotul; Khusnudin, Khusnudin (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
The development of Islamic finance by following today's technology must be considered carefully. need for special attention. The use of technology in Islamic finance is a very significant challenge in adjusting Islamic economic law with implementation in the field. One way to face the current challenges is none other than by following the market share, namely by creating a balance model in transactions. Hybrid Contract (Multi Akad) is a new breakthrough in the application of fiqh muamalah in the contemporary era in Islamic finance. In today's modern era, people tend to prefer using non-cash transactions, one of which is transactions through Sharia cards. This article examines the application of Hybrid contracts to the use of Sharia cards using the literature study research method. The data collection technique is to examine theories or opinions and ideas contained in printed media, especially books and articles or journals that support and are relevant to the issues discussed in the study. The purpose of this study is to analyze the legal theory in the perspective of muamalah fiqh in Islamic economics related to the use of Sharia cards using descriptive library research. By drawing the conclusion that every muamalah activity is permissible as long as there is no law prohibiting it as well as hybrid contract contracts or multi-contracts on Sharia products. Sharia Card is allowed by using kafalah, ijarah, and qardh contracts in it and there is a DSN MUI Fatwa No. 54/DSN-MUI/X/2006 regarding sharia cards: 54/DSN-MUI/X/2006 regarding sharia cards (sharia credit cards) that regulate their use.